Do terrestrial tank bromeliads in Brazil create safe sites for palm establishment or act as natural traps for its dispersed seeds? - Brancalion, Pedro H. S.; Gabriel, Vagner De A. [UNESP]; Gómez, José M. (Wiley, 2009)
This study shows for the first time that terrestrial tank bromeliads from Brazilian restinga can act as natural traps for dispersed palm Euterpe edulis seeds. Such bromeliads, which are shade intolerant, gain benefits by limiting palm recruitment since they hinder canopy formation and, consequently, increase luminosity over its aggregates. © 2008 The Author(s).
Keywords: Atlantic Forest; Euterpe edulis; Facilitation; Plant regeneration; Quesnelia arvensis; Restinga; Seed dispersal; Seed rain; Seedling establishment